THE EFFECT OF BAMBOO DANCING LEARNING MODEL ON STUDENTS’ SPEAKING ABILITY (A Study at The Eleventh Grade Students of SMK Negeri 1 Sarudik 2017/2018 Academic Year) - morgan ganda siahaan (JURNAL LINER (Language Intelligence and Educational Research), 2018)
The purpose of this research is to find: 1)the application of bamboo dancing learning model. 2) the students’ speaking ability before and after using bamboo dancing learning model. 3) the significant effect of bamboo dancing laerning model on students’ speaking ability at the X grade of SMK Negeri 1 Sarudik. Method of the research is experimental. The population of this research are all of the eleventh grade students of SMK Negeri 1 Sarudik. The consist 112 students. Random sampling technique was uses to get a sample the consist 32 students. The technique for collecting data by observation sheet and giving test. The result of the application of Bamboo Dancing Learning Model is 3.6, categorized “Very Good”.The result before using Bamboo Dancing Learning Modelis53.12, categorized “Low”. While the students’ speaking ability after using Bamboo Dancing Learning Model is76.87, categorized “Good”. T-test is 9.24 and t-table is 2.04 it means that there is a significant effect of using Bamboo Dancing Learning Model on students’ speaking ability at the eleventh grade students of SMK Negeri 1 Sarudik2018/2019 Academic Year)